Encouraging Earthquake-Resistant Construction: A Randomized Controlled Trial in Nepal. Issue 4 (November 2016) - Sanquini, Anne M.; Thapaliya, Sundar M.; Wood, Michele M.; Baiocchi, Michael; Hilley, George E.
We created a film designed to accelerate the rate at which communities retrofit or rebuild their school buildings to be earthquake resistant, and tested its effectiveness using a pretest-posttest questionnaire. This theory-based intervention featured local Nepalis who had strengthened their school buildings, as role models to others. Sixteen schools in Kathmandu Valley in need of seismic work were matched into eight pairs. One school in each pair was randomly assigned to view either the intervention film or a placebo film on an unrelated topic. Compared to the control schools, community members who viewed the intervention film statistically significantly increased their pretest-posttest scores on the following factors: (1) earthquake-resistant construction knowledge, (2) belief in its feasibility, (3) intent to support a school strengthening project, and (4) willingness to recommend that others build earthquake-resistant homes.